Explanation of Spiritual Experiences of Mothers of Cancer Children: A Descriptive Phenomenological Study - Neda kalhor; Anahita khodabakhshi-koolaee (Kerman University of Medical Sciences, 2020)
Introduction: The occurrence of ancer in children affects the quality of life of family directly or indirectly. Meanwhile, mothers are the main caregivers and the psychological distress that mothers experience are more than those experienced by other family members. Since in Iran many people resort to spiritual beliefs in dealing with life difficulties, getting aware of the spiritual experiences of mothers of cancer children is very important and useful. Therefore, the objective of this study was to explain the spiritual experiences of mothers of cancer children. Methods: This qualitative study was conducted using a descriptive phenomenological method. The statistical population of the study included mothers of cancer children hospitalized in Mahak Pediatric Cancer Hospital in Tehran in 2018. Twenty mothers were selected using purposive sampling. The data were collected via semi-structrued interviews and data collection continued until theoretical data saturation. The data were analyzed using Colaizzi's seven‐step method. Results: Three main categories and thirteen subcategories were identified in this study. The main categories included "Experiencing spiritual moments and closeness to God", "The mothers' deep psychological and emotional experiences", and "The improvement of family interactions". Conclusion: The results of this study indicated that mothers of cancer children gain valuable spiritual experiences concerning their closeness to God as well as psychological and emotional dimensions. These experiences help to change the view of mothers toward their children's disease.